Assessment Effects of Humidification of Guitars by Complexity Measures of the Sound Level During Sustain - Robert STĘPIEŃ; Piotr WRZECIONO (Archives of Acoustics)
Air humidity significantly affects the sound of wooden instruments. The sound quality decreases when the instrument is exposed to low humidity for an extended period. Therefore, the instrument is treated with a humidifier to improve sound quality. This study aimed to verify the effectiveness of the humidification process by analyzing the quality of guitar sound with the methods used in signal complexity studies, such as Higuchi’s fractal dimension (HFD), symbolic analysis, and empirical mode decomposition (EMD). The sound quality was determined by the sound levels measured before, during, and after the guitars’ humidification. The methods used consistently confirmed the improvement of the guitar sound quality after the humidification process. Moreover, it was concluded that the sound quality changes irregularly during the humidification process.